Second Stage of Visual Perception and Picasso’s Cézannian Cubism - Mallen, Enrique (International Journal of Culture and History, 2023)
Palmer (1999) describes a sequence of four basic stages for visual perception: an im-age-based phase that deals with extracting image structure (primal sketch), a surface-based level which concerns itself with recovering surfaces in depth (2.5-dimensional—henceforth two*-dimensional—sketch), an object-based stage that covers the description of three-dimensional objects (volumetric descriptions), and a category-based phase that handles the identification of objects in terms of known categories. Each of these levels is defined by a different kind of output representation and by the processes that are required to compute it from the input representation. This article points at an interesting parallelism between the surface-based and object-centered stages of vision, and Picasso’s two different phases of Cézannian Cubism. In general terms, it is fascinating to see how an artist’s intuitive approach to pictorial representation appears to mirror scientific research on vision. Cézanne’s influence becomes clear in the spring of 1908 when the Spaniard started applying the familiar Frenchman’s postulates to his work. Despite the fact that the compositions were strictly inscribed on the picture’s flat surface, none of the object’s corporeality was lost, so that one can often speak in terms of “flat relief.” A change occurred between the end of 1908 and the beginning of 1909 when depicted objects became more solid and roundly modeled, and when pure surface representation yielded to attempts at presenting objects in the round. To that extent, we may speak of an object-based stage in Picasso’s output.